1989
DOI: 10.1364/josaa.6.001052
|View full text |Cite
|
Sign up to set email alerts
|

Structure from two orthographic views of rigid motion

Abstract: We study the inference of rigid three-dimensional interpretations for the structure and motion of four or more moving points from but two orthographic views of the points. We develop an algorithm to determine whether image data are compatible with a rigid interpretation. As a corollary of this result we find that the measure of false targets (roughly, nonrigid objects that appear rigid) is zero. We find that if the two views have at least one rigid interpretation, then in fact there is a canonical one-paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 20 publications
3
64
0
Order By: Relevance
“…tain the information to determine whether or not the projections have a rigid interpretation (Bennett, Hoffman, Nicola, & Prakash, 1989;Koenderink & van Doorn, 1991;Ullman, 1977). Ullman (1979) has shown that three parallel projections ofat least four points uniquely define the 3-D structure up to a reflection about the image plane (and a uniform scaling).…”
mentioning
confidence: 99%
“…tain the information to determine whether or not the projections have a rigid interpretation (Bennett, Hoffman, Nicola, & Prakash, 1989;Koenderink & van Doorn, 1991;Ullman, 1977). Ullman (1979) has shown that three parallel projections ofat least four points uniquely define the 3-D structure up to a reflection about the image plane (and a uniform scaling).…”
mentioning
confidence: 99%
“…4 noncoplanar points in 3 views suffice to uniquely determine motion and structure, modulo the unrecoverable signs and values of the overall camera-object distances [16,17,34]. Many algorithms have been published for this problem, including linear methods in [16,20], nonlinear algebric methods in [1,17] and a nonlinear numerical method in [27]. A good review can be found in [27].…”
Section: Minimal Data For Euclidean Reconstructionmentioning
confidence: 99%
“…Some of these theories state the minimal conditions which are necessary to recover a unique structure from general 3-D rigid motion (Huang and Lee, 1989;Longuet-Higgins & Prazdny, 1980;Ullman, 1979) or more constrained motion (Hoffman & Bennett, 1985Hoffman & Flinchbaugh, 1982;Longuet-Higgins, 1982;Webb & Aggarwal, 1981). Other theories describe how the instantaneous 2-D motion limits, but does not uniquely specify, the possible 3-D interpretations (Koenderink & van Doorn 1975, Todd & Bressan, 1990Ullman, 1983) or similarly how 2 discrete views limit the possible interpretations of 3-D shape (Bennett, Hoffman, Nicola & Prakash, 1989;Huang & Lee, 1989, Koenderink & van direction just grazes an object's surface (see Figure 1). These points (the critical set) map onto the viewplane to form a profile ; hence for each possible viewing direction there is a critical set and its corresponding profile.…”
Section: Introductionmentioning
confidence: 99%